Heat transfer and nanofluid flow characteristics through a circular tube fitted with helical tape inserts - Sadeghi, Omidreza (Elsevier Ltd, 2016)
Numerical investigations are performed using finite volume method to study laminar convective heat transfer and nanofluids flows through a circular tube fitted with helical tape insert. The wall of tube was subjected to a uniform heat flux boundary condition. The continuity, momentum and energy equations are discretized and the SIMPLE algorithm scheme is applied to link the pressure and velocity fields inside the domain for plain tube. Four different twist ratios of 1.95-4.89, two different types of nanoparticles, Al2O3 and SiO2 with different nanoparticle shapes of spherical, cylindrical and platelets, and 0.5-2.0% volume fraction in base fluid (water) and nanoparticle diameter in the range of 20-50nm were used to identify their effect on the heat transfer and fluid flow characteristics through a circular tube fitted with helical tape insert geometries. The results indicate that the four types of nanofluid achieved higher Nusselt number than pure water. Nanofluid with Al2O3 particle achieved the highest Nusselt number. For all the cases studied, the Nusselt number increased with the increase of Reynolds number and with the decrease of twist ratio of helical tape insert.